(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
The article addresses one of the most distinctive characteristics of Antoine de Saint-Exupery’s works, namely his ability to efficiently intertwine fiction and reality in his artistic system, which makes the author’s oeuvre appealing to different age groups. The article explores and analyzes the views of domestic and foreign scholars on the philosophical meaning of the "Little Prince" by Antoine de Saint-Exupery, which has firmly established itself in the World Literature school curriculum. The writer’s multifaceted worldview is revealed, and his thoughts and ideas about the essence of things as well as his faith in the great spiritual and intellectual potential of humanity are highlighted. By virtue of generalizing the existing research findings, the problem of fiction and reality in Antoine de Saint-Exupery’s oeuvre is detailed and underpinned.